2014
DOI: 10.1021/jo402665d
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleosides for an Artificially Expanded Genetic Information System

Abstract: Rearranging hydrogen bonding groups adds nucleobases to an artificially expanded genetic information system (AEGIS), pairing orthogonally to standard nucleotides. We report here a large-scale synthesis of the AEGIS nucleotide carrying 2-amino-3-nitropyridin-6-one (trivially Z) via Heck coupling and a hydroboration/oxidation sequence. RiboZ is more stable against epimerization than its 2′-deoxyribo analogue. Further, T7 RNA polymerase incorporates ZTP opposite its Watson–Crick complement, imidazo[1,2-a]-1,3,5-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…[7] More recently, we showed that oligonucleotides built from six-letter AEGIS genetic alphabets can evolve in aD NA matrix under laboratory-created selective pressure to give molecules that bind to breast cancer [14] and liver cancer cells; [15] this success suggested af ull search of the expanded "sequence space" created by the additional genetic "letters". [20] ForR NA,s tructural studies are (if anything) more important than with DNA. [16] In contrast with DNA, RNAhas seldom been examined as amatrix for an expanded genetic alphabet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7] More recently, we showed that oligonucleotides built from six-letter AEGIS genetic alphabets can evolve in aD NA matrix under laboratory-created selective pressure to give molecules that bind to breast cancer [14] and liver cancer cells; [15] this success suggested af ull search of the expanded "sequence space" created by the additional genetic "letters". [20] ForR NA,s tructural studies are (if anything) more important than with DNA. [16] In contrast with DNA, RNAhas seldom been examined as amatrix for an expanded genetic alphabet.…”
mentioning
confidence: 99%
“…Recent results showed that T7 RNAp olymerase can generate RNA molecules containing Z and P AEGIS ribonucleosides from encoding GACTZP DNAm olecules,a nd reverse transcriptase can synthesize Z and P AEGIS DNAf rom complementary GACUZP AEGIS RNA. [20] ForR NA,s tructural studies are (if anything) more important than with DNA. Because of its extra 2'-hydroxy group,R NA has many more conformational opportunities than DNA.…”
mentioning
confidence: 99%
“…Only recently was this work extended to the enzymology of the pair between 6‐amino‐5‐nitro‐3‐(1′‐β‐ D ‐ribofuranosyl)‐2(1 H )‐pyridone and 2‐amino‐8‐(1′‐β‐ D ‐ribo‐furanosyl)‐imidazo‐[1,2‐a]‐1,3,5‐triazin‐4‐(8 H )‐one, called Z and P (Figure 1, right box). Recent results showed that T7 RNA polymerase can generate RNA molecules containing Z and P AEGIS ribonucleosides from encoding GACT ZP DNA molecules, and reverse transcriptase can synthesize Z and P AEGIS DNA from complementary GACU ZP AEGIS RNA 20…”
Section: Data Collection and Refinement Statisticsmentioning
confidence: 99%
“…Benner and coworkers, as part of their long-term goal of developing a high-fidelity expanded genetic alphabet as described above, recently evolved a Taq polymerase variant capable of efficiently amplifying sequences containing the artificial Z:P base pair, which relies on an unnatural hydrogenbonding pattern [39]. In addition, they have demonstrated that Z and P can be incorporated into RNA transcripts, a key milestone in the step towards their potential use for genetic code expansion [40,41 ]. Recently, the Brakmann laboratory realised a long sought goal of engineering a T7 polymerase capable of synthesising RNA modified with all four 2 0 -O-methyl nucleotides [42].…”
Section: Enzymatic and Non-enzymatic Replicationmentioning
confidence: 99%